The abuse of the dominant position in the National Civil and Commercial Code and its effects in the Argentinian Competition Law - Darsaut, Maria Victoria (Universidad Nacional del Litoral, 2020)
The regulation about the abuse of dominant position in the market in the National Civil and Commercial Code is the front door for the private enforcement of Competition Law in Argentina.This article will address the specific regulations and the contribution of doctrine and jurisprudence about the topic.